2021
DOI: 10.1177/0003489420987426
|View full text |Cite
|
Sign up to set email alerts
|

Tracheocutaneous Fistula After Pediatric Open Airway Reconstruction

Abstract: Objectives: Tracheocutaneous fistula (TCF) is a common occurrence after pediatric tracheostomy decannulation. However, the persistence of TCF after staged reconstruction of the pediatric airway is not well-described. The primary objective was to determine the rate of persistent TCF after successful decannulation in children with staged open airway reconstruction. Methods: A case series with chart review of children who underwent decannulation after double-stage laryngotracheal reconstruction between 2017 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The observed rate of two‐thirds is consistent with recent series suggesting a frequency as high as 57% 4,9 . The only data suggesting a higher TCF rate was in a report of successfully decannulated children after laryngotracheal reconstruction where 85% developed a persistent TCF 16 . Recognizing the frequency of a persistent TCF guides management decisions after decannulation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The observed rate of two‐thirds is consistent with recent series suggesting a frequency as high as 57% 4,9 . The only data suggesting a higher TCF rate was in a report of successfully decannulated children after laryngotracheal reconstruction where 85% developed a persistent TCF 16 . Recognizing the frequency of a persistent TCF guides management decisions after decannulation.…”
Section: Discussionsupporting
confidence: 85%
“…4,9 The only data suggesting a higher TCF rate was in a report of successfully decannulated children after laryngotracheal reconstruction where 85% developed a persistent TCF. 16 Recognizing the frequency of a persistent TCF guides management decisions after decannulation. Given the physiologic and cosmetic impact of a persistent communication between the trachea and the external environment, close monitoring to ensure closure after decannulation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest the rate of TCF following decannulation to be between 49% and 65% [31,32],33]. In patients decannulated following double-stage open airway reconstruction, the incidence has been found to be as high as 85% [34]. The most commonly identified risk factor related to TCF formation is duration of tracheostomy, with a cannulation period of over 24 months being most strongly correlated [31,32,33].…”
Section: Tracheocutaneous Fistulamentioning
confidence: 99%
“…29 In addition to these individuals requiring short-or long-term management with tracheostomy, as many as 70% of adults and children with a tracheostomy for more than 16 weeks will experience a persistent tracheocutaneous fistula that typically requires 1 or more surgical procedures to repair. [29][30][31] The pathophysiology of irritant contact dermatitis created when skin is exposed to respiratory secretions is not known. Research concerning the prevalence of peristomal irritant contact dermatitis is also sparse; a single report in Chinese indicated a 38.5% prevalence of respiratory secretion irritant contact dermatitis in persons with tracheostomies.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…Similarly, Branco's group30 reviewed medical records of 5265 patient with cervical spinal cord injuries and reported that 20.6% required long-term tracheostomy for ventilatory support 29. In addition to these individuals requiring short- or long-term management with tracheostomy, as many as 70% of adults and children with a tracheostomy for more than 16 weeks will experience a persistent tracheocutaneous fistula that typically requires 1 or more surgical procedures to repair 29–31…”
Section: Irritant Contact Dermatitis Due To Respiratory Secretions (I...mentioning
confidence: 99%